The Relationship between Discrepancies in Career Anchors of Information Technology Personnel and Career Satisfaction - Ling-Hsing Chang; Sheng Wu (Behavioral Sciences, 2023)
The career anchors of information technology personnel (ITP) are critical factors influencing their career satisfaction (CS), and these factors are also influenced by national culture. Although a number of scholars have studied the internal CS of employees, these scholars have not explained how to increase the CS of ITP from both individual and organizational perspectives and to further improve the success rate of IS projects. Thus, this study adopts the goal–achievement gap (discrepancy) theory to explore the gap between the “internal career desires (career wants, CW)” and “external career opportunities (career have, CH)” of ITP in two different cultural societies, namely mainland China and the United Arab Emirates, and whether the gap impacts their CS. The data in this study were collected from the Internet. A survey was posted on Internet discussion forums for full-time ITP participants within organizations in China and the United Arab Emirates; thus, the results of this study are possibly only generalizable to these two countries. Finally, the results of this study provide the following contributions: (1) There are 13 career anchors (technical competence, managerial competence, autonomy, organizational stability, challenge, lifestyle, identity, creativity, variety, service, entrepreneurship, geographic security, and learning motivation) of ITP in China, which can be divided into three categories, and these are totally different from the four categories identified by ITP in the United Arab Emirates. (2) The surface analysis approach (RSA) to test the curvilinear relationship between the CW, CH, and CS of ITP indeed can explain more than the linear SEM (structural equation modeling) test between the CW and CS, CH, and CS separately, both tests are in two different cultural societies, China and the United Arab Emirates.